2016
DOI: 10.3310/hsdr04140
|View full text |Cite
|
Sign up to set email alerts
|

Equity of utilisation of cardiovascular care and mental health services in England: a cohort-based cross-sectional study using small-area estimation

Abstract: BackgroundA strong policy emphasis on the need to reduce both health inequalities and unmet need in deprived areas has resulted in the substantial redistribution of English NHS funding towards deprived areas. This raises the question of whether or not socioeconomically disadvantaged people continue to be disadvantaged in their access to and utilisation of health care.ObjectivesTo generate estimates of the prevalence of cardiovascular disease (CVD) and common mental health disorders (CMHDs) at a variety of scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 368 publications
0
8
0
Order By: Relevance
“…Area deprivation may impact the number of people in contact with mental health services through affecting both the prevalence of mental disorders and health service utilization. Higher deprivation can result in higher use of formal services through increased comorbidity [ 32 ] [ 33 ], reduced social support [ 34 ] or reduced availability of non-healthcare resources to draw from [ 22 ]. There is evidence from literature that areas with higher deprivation have a higher number of compulsory admissions to mental health hospitals [ 35 ], for example, one additional percentage point in population income deprivation (according to the European Deprivation Index definition) has previously been shown to be associated with a 1.6% increase in admissions to hospital with severe mental illness [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Area deprivation may impact the number of people in contact with mental health services through affecting both the prevalence of mental disorders and health service utilization. Higher deprivation can result in higher use of formal services through increased comorbidity [ 32 ] [ 33 ], reduced social support [ 34 ] or reduced availability of non-healthcare resources to draw from [ 22 ]. There is evidence from literature that areas with higher deprivation have a higher number of compulsory admissions to mental health hospitals [ 35 ], for example, one additional percentage point in population income deprivation (according to the European Deprivation Index definition) has previously been shown to be associated with a 1.6% increase in admissions to hospital with severe mental illness [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fact that areas with a higher proportion of the population who are BAME had lower service use, after the prevalence of mental disorders is taken into account, suggests that there may be differences in access to services related to ethnicity. It has been previously found that people of black African or Caribbean backgrounds are overrepresented in inpatient mental health services but underrepresented in community services [ 22 ], and that Black patients may need to navigate more complex care pathways before being accepted by secondary mental health services [ 39 ]. In contrast those from Asian backgrounds have been previously found to use inpatient units less than White patients [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Novel data linkageslinking health to survey data with better socioeconomic measures or even to robustly anonymised Census outputis one way forward. [46][47][48] There might also be scope to identify educational and occupational status from electronic health and other records. 49 However, this approach is currently accompanied by substantial practical and ethical challenges.…”
Section: Aetiology Prevention Of Disease and Promotion Of Well-beingmentioning
confidence: 99%